Activatable Sulfur Dioxide Nanosonosensitizer Enables Precisely Controllable Sono‐Gaseous Checkpoint Trimodal Therapy for Orthotopic Hepatocellular Carcinoma - Jing Liang; Guangwen Cheng; Luping Qiu; Liyun Xue; Huning Xu; Xiaohui Qiao; Na Guo; Huijing Xiang; Yu Chen; Hong Ding (Advanced Science)
Abstract Immune checkpoint blockade (ICB) is combined with sonodynamic therapy (SDT) to increase response rates and enhance anticancer efficacy. However, the “always on” property of most sonosensitizers in reducing tumor microenvironment (TME) compromises the therapeutic outcome of sonoimmunotherapy and exacerbates adverse side effects. Precisely controllable strategies combining sulfur dioxide (SO2) gas therapy with cancer immunotherapy can address these issues but remain lacking. Herein an “activatable SO2 nanosonosensitizer” for precise sono‐gaseous checkpoint trimodal therapy of orthotopic hepatocellular carcinoma (HCC) is reported, whose full activity is initiated by ultrasound (US) irradiation in the reducing TME. This “activatable SO2 nanosonosensitizer,” Aza‐DNBS nanoparticles (NPs), are established by self‐assembling Aza‐boron‐dipyrromethene based sonosensitizer molecules and 2,4‐dinitrobenzenesulfonate (DNBS)‐caged SO2 prodrug. The activity of Aza‐DNBS NPs is initially silenced, and the sonodynamic, gaseous, and immunosuppressive TME reprogramming activities are precisely awakened under US irradiation. Due to the glutathione‐responsiveness of Aza‐DNBS NPs, Aza‐DNBS NPs can generate large amounts of SO2 for gas therapy‐enhanced SDT, which triggers robust immunogenic cell death activation and reprogramming of the immunosuppressive TME, thereby significantly suppressing orthotopic tumor growth and delaying lung metastasis. Thus, this study represents a strategy for designing a generic nanoplatform for precisely combined immunotherapy of orthotopic HCC.